Influence of Processing on the Microstructure and the Mechanical Properties of Zn/HA8 wt.% Biodegradable Composite - Pinc, Jan; Miklášová, Eva; Průša, Filip; Čapek, Jaroslav; Drahokoupil, Jan; Vojtěch, Dalibor (Manufacturing Technology Journal, 2019)
Zinc-based materials show large potential to become biodegradable materials with ideal corrosion behavior in the body environment. In this study, a zinc composite containing 8 wt. % of hydroxyapatite (HA) was prepared by spark plasma sintering (SPS) and characterized from a point of view of the microstructural and mechanical properties. The influence of pre-processing (milling) of the powders on the microstructure after the sintering was studied. The materials prepared by the milling and subsequent sintering showed insufficient cohesion due to the wrapping of Zn by HA particles and possible oxidation of zinc particles. Compressive and flexural tests of sintered materials prepared without any pre-processing confirmed the role of hydroxyapatite as a defect in the Zn/HA8_SPS structure. The results of the hardness measurement suggest that the HA does not affect the behavior of the zinc matrix.
Keywords: Zinc; Hydroxyapatite; Biodegradable composites; Ball milling; Spark plasma sintering